The Africans: A triple heritage : A Legacy of lifestyles - Mazrui, Ali AlAmin (The Annnenberg/CPB Collection, 1986)
Explores how contemporary African lifestyles are influence by indigenous, Western and Islamic factors. Examines the role of women and the family in various African societies. A view of the continent from the inside looking out Commentary by Ali A. Mazrui. Target audience: Senior high school through college students and adults. In English with portions in African dialects with English subtitles.